Pengembangan Aplikasi Pembelajaran Berbasis Android Materi Geometri Fase A Kurkulum Merdeka - Henry Zazin Afidin; Nursiwi Nugraheni (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
This research aims to develop learning media based on android applications, which can be used as a support for learning geometry material phase A Kurikulum Merdeka. The learning media created combines the concept of learning and practicing directly. Where through this media students can interact directly with the material. The achievements of this research: (1) Developing android-based learning media products that can be used as a means of supporting learning. (2) Knowing the process of developing android applications that are in accordance with the geometry material phase a independent curriculum. (3) Knowing the impact of the implementation of android-based geometry learning media on student learning outcomes. The test subjects in this study were second grade students of SD Negeri 2 Sokaraja. The model used in this research is the Plomp & Nieveen (2010) development model. The result of this research is an android-based learning media named as